Role of Chitin-Binding Proteins in the Specific Attachment of the Marine Bacterium Vibrio harveyi to Chitin - Montgomery, Michael T. (1993)
We examined the mechanism of attachment of the marine bacterium Vibrio harveyi to chitin. Wheat germ agglutinin and chitinase bind to chitin and competitively inhibited the attachment of V. harveyi to chitin, but not to cellulose. Bovine serum albumin and cellulase do not bind to chitin and had no effect on bacterial attachment to chitin. These data suggest that this bacterium recognizes specific attachment sites on the chitin particle. The level of attachment of a chitinase-overproducing mutant of V. harveyi to chitin was about twice as much as that of the uninduced wild type. Detergent-extracted cell membranes inhibited attachment and contained a 53-kDa peptide that was overproduced by the chitinase-overproducing mutant. Three peptides (40, 53, and 150 kDa) were recovered from chitin which had been exposed to membrane extracts. Polyclonal antibodies raised against extracellular chitinase cross-reacted with the 53- and 150-kDa chitin-binding peptides and inhibited attachment, probably by sterically hindering interactions between the chitin-binding peptides and chitin. The 53- and 150-kDa chitin-binding peptides did not have chitinase activity. These results suggest that chitin-binding peptides, especially the 53-kDa chitin-binding peptide and chitinase and perhaps the 150-kDa peptide, mediate the specific attachment of V. harveyi to chitin.